Mergers & acquisitions research: A bibliometric study of top strategy and international business journals, 1980–2010 - Ferreira, Manuel Portugal (2018)
Mergers and acquisitions (M&As) are important modes through which firms carry out their domestic and international strategies and have been noted as the CEOs favorite strategy. As a significant field of study, M&Aresearch has accumulated substantial knowledge. This bibliometric study examines the extant strategy and international business literature on M&As. Methodologically, we examined a sample of 334 articles published in sixteen leading management/business journals, during a 31 year period — from 1980 to 2010. The results provide a global perspective of the field, identifying the works that have had the greater impact, the intellectual interconnections among authors and works, the main research traditions, or themes, delved upon on M&Arelated research. Structural and longitudinal analyses reveal the changes in the intellectual structure of the field over time. A discussion on the accumulated knowledge and future research avenues concludes this paper.